Analisis Life Cycle Assessment (LCA) Produksi Tahu Bakso Skala Rumahan: Dampak Lingkungan dan Solusi - Mustapa, Alan; Putri, Dian Khoiriyani; Hakim, Muh. Adrikni Al; Pujiati, Amin; Melati, Inaya Sari (Universitas Nurul Jadid, 2025)
The home-based food industry, including tofu and meatballs, plays an important role in supporting the local economy and overcoming environmental poverty challenges. This study aims to analyze the environmental impact of home-based tofu and meatball production using ISO and OpenLCA standards. The analysis covers all stages of production, from raw material acquisition, washing, grinding, mixing, filling, steaming, to cooling. The Life Cycle Inventory (LCI) results show that each stage contributes to the use of energy, air, and raw materials, with the steaming process having the greatest impact on the most dominant category compared to other stages. Recommended measures include energy efficiency through heat insulation and biogas use, selection of local suppliers, use of low-chemical raw materials, air washing recycling, and utilization of organic waste for compost or biogas. This study proves the need for sustainable production strategies in the home-based food industry, not only to minimize environmental impact, but also to strengthen competitiveness and local economic sustainability.